ANALISIS PEMASARAN USAHA PEMBUATAN TAHU PADA UD. TAHU ANYAR (Studi Kasus) DI KELURAHAN GUNTUNG PAYUNG KECAMATAN LANDASAN ULIN KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Wasdiyanta; Ahmad Baparki; Zuraida (Chlorophyl, 2022)
This research was conducted in the Guntung Payung Village with the aim of knowing the pattern of marketing channels, knowing farmer`s marketing share and knowing the marketing efficiency of UD's tofu. New Know. The type of data collected in this paper is primary data and secondary data. The research method used is the case study method. There are 3 marketing channels. The lowest Farmer's share is in the first channel which is 68.13% and the highest marketing efficiency is in the third channel which is 3.33%